Waqf in Malaysia: the power behind it / Dahlia Ibrahim - Ibrahim, Dahlia (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The waqf institutions' situation in Malaysia long before independence is very different from today's scenario. Back then, many Muslims concentrated on preserving their religious customs from being contaminated by the British nonspiritual procedures. During this colonial era, the waqif personally and directly appointed many highly reputed individuals such as the village head, religious school teachers, mosques and suraus to manage the waqf. The original owner did not make any official ownership transfers with the mutawalli; there was only verbal agreement between the two parties (Mahamood, 2006). Therefore, there was no proof as to the right of the waqf for the intended purpose when the founders normally left it to the trusted individuals to fully manage the waqf as long as the trusted mutawalli deliver the intended purpose accordingly. To overcome this situation, the State Islamic Religious Council (SIRC) of each state in Malaysia is given the power and trust to administer the waqf, replacing the old ways in the appointment of trusted individuals by the founders. The SIRC was set up way back in 1916 where it was originally established merely for the supervision of mosques in Kelantan. As the sole trusteeship of the waqf, each SIRC in each state in Malaysia is given the authority to supervise, manage and develop all the waqf (Mahamood, 2006).